A Flexible, Highly Sensitive, and Selective Chemiresistive Gas Sensor Obtained by In Situ Photopolymerization of an Acrylic Resin in the Presence of MWCNTs. Issue 2 (17th October 2018) - Vigna, Lorenzo; Fasoli, Andrea; Cocuzza, Matteo; Pirri, Fabrizio C.; Bozano, Luisa D.; Sangermano, Marco
Abstract: A new flexible polymeric gas sensor is developed by photocrosslinking poly(ethylene glycol) diacrylate resin (PEGDA) containing multi‐walled carbon nanotubes (MWCNTs) as conductive filler. The cured material shows a percolative threshold conductivity which changes when in contact with various gas analytes with different chemical and physical properties. The different behavior of the sensors toward the different gases is explained either on the basis of chemical affinity toward the polymeric matrix or due to the interactions that can occur between the analyte and the surface of the nanotubes in the case of the aromatic gas. Abstract : A new flexible polymeric gas sensor is developed by photocrosslinking poly(ethylene glycol) diacrylate resin (PEGDA) containing multi‐walled carbon nanotubes (MWCNTs) as conductive filler. The cured material shows a percolative threshold conductivity which changes when in contact with various gas analytes with different chemical and physical properties.